2022
DOI: 10.3389/fimmu.2022.885280
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Microenvironment: Interactions Between Innate Immune Cells and Developing Thymocytes

Abstract: The thymus is a crucial organ for the development of T cells. T cell progenitors first migrate from the bone marrow into the thymus. During the journey to become a mature T cell, progenitors require interactions with many different cell types within the thymic microenvironment, such as stromal cells, which include epithelial, mesenchymal and other non-T-lineage immune cells. There are two crucial decision steps that are required for generating mature T cells: positive and negative selection. Each of these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Successful TCR β chain rearrangement delivers proliferation signals and instructs the transition of DN cells into DP cells. This event is followed by positive selection by thymic epithelial cells (TECs) in the cortex and negative selection by DCs in the medullary region, responding to strong TCR-MHC interactions ( 28 ). Those DP cells with non-functional TCR-MHC interactions undergo death by neglect, which occurs for over 95% of DPs ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful TCR β chain rearrangement delivers proliferation signals and instructs the transition of DN cells into DP cells. This event is followed by positive selection by thymic epithelial cells (TECs) in the cortex and negative selection by DCs in the medullary region, responding to strong TCR-MHC interactions ( 28 ). Those DP cells with non-functional TCR-MHC interactions undergo death by neglect, which occurs for over 95% of DPs ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the role of DCs in thymic T cell development, controversial reports have been made. On one side, thymic DCs have been deemed as a major player that mediates negative selection to induce the apoptosis of DP cells ( 28 , 30 , 31 ); on the other side, thymic DCs were also reported to be involved in positive selection, thus to maintain the survival of DP cells ( 32 , 33 ). The discovery that CD11c plays an essential role in maintaining the survival of T cells suggests that, in addition to MHC-II molecule, DCs could use CD11c to maintain T cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…These intricate selection processes rely on the precise organization and compartmentalization of parenchymal cells facilitating interactions and signaling pathways inside the thymus ( 39 ). The thymic microenvironment includes nerves/nerve fibers, which are believed to regulate T cell development and thymic endocrine function by influencing the secretion of self-hormones such as thymulin, thymopoietin, and thymosins ( 40 , 41 ).…”
Section: Neuroimmune Interactions In Primary Lymphoid Organs In Healt...mentioning
confidence: 99%
“…The thymus plays a crucial role in the differentiation and development of T-cells and is the residence of many cell types. 46 A variety of immune cells reside in the spleen, such as neutrophils, macrophages, natural killer (NK) cells, monocytes, dendritic cells (DCs) and gamma delta (γδ) T cells. 47 A study reported that the overexpression of TNF-α led to spleen inflammation in the laying hen, causing spleen damage.…”
Section: Egcg Increases Spleen Index and Thymus Indexmentioning
confidence: 99%